The Ameliorative Role of Acacia senegal Gum against the Oxidative Stress and Genotoxicity Induced by the Radiographic Contrast Medium (Ioxitalamate) in Albino Rats - Islam El-Garawani; Sobhy Hassab El-Nabi; Ahmed El Kattan; Azza Sallam; Sabha Elballat; Shaimaa Abou-Ghanima; Islam H. El Azab; Hesham R. El-Seedi; Shaden A. M. Khalifa; Sawsan El-Shamy (MDPI AG, 2021)
Arabic gum (Acacia senegal, AG) is proven effective antioxidant and cytoprotective agent. The present study was designed to test this notion by investigating the possible role of AG against the radiographic contrast medium (Ioxitalamate, Telebrix-35®, TBX)-induced oxidative stress and genotoxicity. Albino rats were divided into four groups and supplied with either; distilled water, daily 10% (w/v) AG, an intravenous dose of TBX (1600 mg I/kg b.wt) and co-administration of TBX and AG. Rats were sacrificed and blood samples were collected to assess the genotoxicity employing the peripheral blood leucocytes fluorescent double staining; namely the acridine orange/ethidium bromide (AO/EB) staining and alkaline comet assay. Further, chromosomal analyses were done in bone marrow cells. Serum urea and creatinine levels, in addition to malondialdehyde (MDA), nitric oxide (NO), catalase (CAT) and glutathione (GSH) levels in kidney tissues were measured. Liquid chromatography-mass spectrophotometry (LC-MS-MS) was performed to identify the chemical composition of AG extract. Kidney functions, single/double-stranded DNA damage, chromosomal aberrations, mitotic index, MDA and NO levels were significantly (p < 0.001) increased in TBX-treated group compared to the control and AG-treated one. Meanwhile, CAT and GSH activities were significantly diminished and the AG supplementation significantly (p < 0.001) ameliorated these effects compared with the control and AG-treated groups. Five compounds have been identified using GNPS networking including 7,3',4'-Trihydroxyisoflavone, Noscapine, Tetrahydropapaveroline, Costunolide, Hesperidin. In conclusion, results of the present study suggest that AG exerted a protective role against TBX-induced oxidative stress and genotoxicity which may be attributed to the active metabolites in the gum.